BACTERIAL QUALITY OF DIFFERENT BRANDS OF SACHET WATER SOLD IN FEDERAL UNIVERSITY OF TECHNOLOGY CAMPUS, IMOSTATE, NIGERIA - R.I, Okechuwu; H.U., Anuforum; O.C., Ezea; O.O., Igboasoiyi (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Drinking water regulations require that potable water for human consumption be free from human disease-causing bacteria and specific indicator bacteria such as coliforms and E. coli. Under total asepsis and using standard procedures bacterial analysis of the Six (6) brands sachet of water produced from FUTO campus were done. The different brands of sachet water analysed were devoid of coliforms and E. coli which indicates that the laboratories for the production of these sachet water to a good extent are kept in good conditions that do not encourage bacteria growth. However, after 72hrs micro-organisms grew on all the sachet water samples except in malyn sachet. Results of total bacteria content of the water samples showed that malyn sachet water has the lowest with 27 x 10-1 cfu/ml and Aljonlife sachet water had the highest with 328 x 10-1 cfu/ml. Bacillus subtilis and Staphylococcus epidermis were detected. This is of public health significance. National Agency for Food and Drugs Administration and Control (NAFDAC) should embark upon routine unannounced checks, monitoring the production processes of sachet water by their producers. Also random testing of market samples will be a good way of detecting whether the water quality is meeting the required standards.